Decomposition of Fuzzy Automata based on Lattice-Ordered Monoid (Global Journal of Science Frontier Research, 2018)
The purpose of the present work is to introduce decomposable concepts of fuzzy automaton having the membership values in the lattice-ordered monoids. Unlike to the usual fuzzy automata, we show that such concepts for fuzzy automata having the membership values in lattice-ordered monoids by the associated monoid structure.
Keywords: lattice-ordered monoid; fuzzy automaton; primary; f-primary; decomposition